Implementation of Calculation of Cost of Goods Production by Full Costing and Variable Costing Methods (Case Study of MSMEs in the Food Sector in Jambi City) - Halim, Abdul; Rico Wijaya Z; Reni Yustien (Indonesian Journal of Economic & Management Sciences, 2024)
Struggle and careful planning are the keys to the company's development in facing various problems and market competition. In the production context, determining the cost of production (HPP) is a critical factor that influences company profits. In the paragraph above, methods for determining COGS, such as full costing and variable costing, are discussed to minimize errors in determining product selling prices. The importance of efficiency in calculating production costs is emphasized, especially for micro, small and medium enterprises (MSMEs), which often lack accuracy in determining the selling price of their products. A case study of MSMEs in Jambi City shows that manual recording of costs of goods manufactured needs to be improved to avoid errors and guarantee profits that are in line with expectations. By using the right methods, MSMEs can increase their competitiveness and achieve success in a competitive market